2021
DOI: 10.3390/coatings11121498
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 1060, 2024 and 7075 Aluminum Alloy Anodic Oxide Films

Abstract: On aluminum alloys of grades 1060, 2024 and 7075, regular and highly uniform oxide films were formed by anodic oxidation. Anodizing was carried out at a constant pressure in a phosphoric acid solution of various concentrations. Using scanning electron microscopy (SEM) and X-ray diffraction (XRD), the optimal characteristics of the method of anodic oxidation for forming uniform oxide films on aluminum alloys were determined: anodic oxidation time, temperature, voltage and the concentration of H3PO4. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…First, during the micro-PAO process, the large amount of oxygen bubbles generated in the anodic zone filled with AFP was inconsistent with the few bubbles that should be produced by the main anodic reaction in FEODT. 30,33 Furthermore, the morphology of the samples prepared via micro-PAO was not interpretable by FEODT. 34 In particular, the pore rings on the surfaces of the samples prepared for 120 s revealed that the pore growth was clearly an inside-to-outside tendency for the oxide inside the channel to be extruded outside on the surface, as depicted in Figure 1f.…”
Section: Resultsmentioning
confidence: 98%
“…First, during the micro-PAO process, the large amount of oxygen bubbles generated in the anodic zone filled with AFP was inconsistent with the few bubbles that should be produced by the main anodic reaction in FEODT. 30,33 Furthermore, the morphology of the samples prepared via micro-PAO was not interpretable by FEODT. 34 In particular, the pore rings on the surfaces of the samples prepared for 120 s revealed that the pore growth was clearly an inside-to-outside tendency for the oxide inside the channel to be extruded outside on the surface, as depicted in Figure 1f.…”
Section: Resultsmentioning
confidence: 98%
“…The use of alloying components makes it possible to improve the quality of aluminum products and avoid some of the disadvantages inherent in the pure metal. The electrochemistry of aluminum alloys is also the subject of intensive and versatile research [23,[26][27][28][29][30][31][32]. The surface properties of anodized aluminum and its alloys, including microstructural parameters [23,[33][34][35], wettability [36,37], mechanical [38,39] and corrosion stability [39][40][41][42][43][44], coloring [26,45] and other aspects [42,[46][47][48], are actively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Deep neural networks (DNNs) have been proven to be effective in a wide range of applications, e.g., speech recognition, image classification, and medical diagnostics [1,2]. With the advance in deep learning technology and the popularity of open source, the industry companies can directly download the pre-trained model deep neural networks from public model zoos such as Model Zoo [3] and Model Depot [4] for their specific tasks.…”
Section: Introductionmentioning
confidence: 99%